Graphic organizers as a cognitive strategy to develop vocabulary among ninth-year a students at unidad educativa del milenio Bernardo Valdivieso of the city of loja during the 2016 – 2017 school year - Jimenez Armijos, Hernan Ezequiel (2018)
The main objective of the research was to develop the vocabulary through graphic organizers as a cognitive strategy. The methods used were; scientific method that refers to the series of steps that must be followed to obtain a valid knowledge; descriptive method, deals with data and characteristics of a population; statistical method in which the researcher collects and analyzes all the answers represented in graphs to indicate the percentages and results of the instruments; and finally the synthetic-analytical method, which is responsible for studying the facts, starting from the decomposition of the object of study. The instruments used for data collection were observation sheets, eight-week intervention plan, field journals, tests and questionnaires that were applied to 41 ninth-grade students of basic education. In conclusion, the research results showed that graphic organizers as a cognitive strategy significantly develop vocabulary, mainly in the most important aspects that are form, meaning and use.